Книга трех: сказочная хроника / Л. Александер - Александер Ллойд (Замок чудес, 1995)
Экземпляры: аб. (2006) / Инвентарный номер: 41931 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: А 46 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-4